Clinical Features of the Course of Rapidly Progressive Periodontitis Combined with Bronchial Asthma and the Effects of Various Modes of Complex Therapy (Texas Journal of Medical Science, 2023)
The aim of the research was to study the clinical features of the course of rapidly progressive periodontitis (RPР) combined with bronchial asthma and the effects of complex therapy. In the dynamics of the complex treatment, including propolis and resonance therapy against the background of basic treatment, a significant improvement in microcirculation and the degree of restoration of trophic disorders of the periodontal part of the teeth was established. Also, in these patients, the FVD indicators significantly increased.